Accelerating the change in China’s economic growth model under the influence of the digital economy - Rong, Li; Gospodarik, Catherine G. (Journal of the Belarusian State University. Economics, 2022)
Under the influence of the new situation, China has moved from a traditional economic model to a digital economy model. The digital economy and the dynamics of China’s economic development are analysed. Transition under study from traditional to modern services, from factors of production to innovation, from investment to consumption, from demand to supply and from high-carbon to low-carbon foreign trade. The shortcomings of China’s economic development are considered. The way of optimising the digital economy to accelerate the change in the model of the dynamics of China’s economic development is being explored.
Keywords: digital economy; economic growth; Chinese economic model; transformation; GDP growth